Stenotrophomonas maltophilia Phenotypic and Genotypic Diversity during a 10-year Colonization in the Lungs of a Cystic Fibrosis Patient - Pompilio, Arianna; Crocetta, Valentina; Ghosh, Dipankar; Chakrabarti, Malabika; Gherardi, Giovanni; Vitali, Luca Agostino; Fiscarelli, Ersilia; Di Bonaventura, Giovanni (Frontiers in Microbiology, 2016)
The present study was carried out to understand the adaptive strategies developed by S. maltophilia for chronic colonization of the cystic fibrosis (CF) lung. For this purpose, 12 temporally isolated strains from a single CF patient chronically infected over a 10-year period were systematically characterized for growth rate, biofilm formation, motility, mutation frequencies, antibiotic resistance, and pathogenicity. Pulsed-field gel electrophoresis showed over time the presence of 2 distinct groups, each consisting of 2 different pulsotypes. The pattern of evolution followed by S. maltophilia was dependent on pulsotype considered, with strains belonging to pulsotype 1.1 resulting to be the most adapted, being significantly changed in all traits considered. Generally, S. maltophilia adaptation to CF lung leads to increased growth rate and antibiotic resistance, whereas both in vivo and in vitro pathogenicity as well as biofilm formation were decreased. Our results show for the first time that S. maltophilia can successfully adapt to a highly stressful environment such as CF lung by paying a “biological cost”, as suggested by the presence of relevant genotypic and phenotypic heterogeneity within bacterial population. This indicates that S. maltophilia populations are significantly more complex and dynamic than can be described by the analysis of any single isolate and can fluctuate rapidly to changing selective pressures.